Open access datasets from the Antarctic Circumnavigation Expedition - Thomas, Jen (Zenodo, 2021)
The Antarctic Circumnavigation Expedition (ACE; https://spi-ace-expedition.ch ) brought together 22 distinct science projects, collecting around 30 TB of data and almost 30,000 samples. A custom-built tool was built to record all data and sample collection on board. Open access datasets from the expedition continue to be published: https://zenodo.org/communities/spi-ace . This poster, presented at IMDIS 2021 ( https://imdis2021.seadatanet.org/ ), briefly describes the tool that was created and outlines the published datasets. The Antarctic Circumnavigation Expedition was made possible by funding from the Swiss Polar Institute and Ferring Pharmaceuticals.